Polymerase δ replicates both strands after homologous recombination-dependent fork restart - Miyabe, Izumi (Nat Struct Mol Biol, 2015)
To maintain genetic stability DNA must be replicated only once and replication completed even when individual replication forks are inactivated. Because fork inactivation is common, the passive convergence of an adjacent fork is insufficient to rescue all inactive forks. Thus, eukaryotic cells have evolved homologous recombination-dependent mechanisms to restart persistent inactive forks. Completing DNA synthesis via Homologous Recombination Restarted Replication (HoRReR) ensures cell survival, but at a cost. One such cost is increased mutagenesis caused by HoRReR being more error prone than canonical replication. This increased error rate implies that the HoRReR mechanism is distinct from that of a canonical fork. Here we exploit the fission yeast Schizosaccharomyces pombe to demonstrate that a DNA sequence duplicated by HoRReR during S phase is replicated semi-conservatively, but that both the leading and lagging strands are synthesised by DNA polymerase delta.